Preliminary study of modified asphalt binders with thermoplastics: The Rheology properties and interfacial adhesion between thermoplastics and asphalt binder. (27th September 2021) - Chen, Siyu; Che, Tiankai; Mohseni, Alaeddin; Azari, Haleh; Heiden, Patricia A.; You, Zhanping
Highlights: Maleated asphalt binder modification with the thermoplastics. Rheology properties between thermoplastics and asphalt binder. Increased high-temperature PG for all tested plastic modified binders. Abstract: In recent decades, polymer-modified asphalt materials have been used in response to increased traffic on the roads. The main objective of this paper is to explore the modification effect of thermoplastics on asphalt binders and investigate the effectiveness of maleic anhydride in improving interfacial adhesion. Three different thermoplastics were used with a dosage of 4 wt%. and a co-reactant maleic anhydride was added with a content of 2 wt% by weight of the binder. The thermoplastics showed a great improvement on high-temperature performance grade (PG) and a slight decrease on low-temperature PG. In addition, the usage of maleic anhydride enhanced the high performance PG on all plastic modified binders. With the addition of maleic anhydride, the binders increased a few degrees of higher temperature, indicating an improvement in compatibility. The compatibility improvement may be related to form a copolymer where maleic anhydride modified with different asphalt components. With the addition of maleic anhydride, the J nr decreased and the percent recovery increased, which showed a better interaction between plastic and asphalt binders. High-temperature PG results in Unified Performance Tests by incremental Method (UPTiM) were strongly connected with J n r 3.2 in Multiple Stress Creep Recovery test with a power fit trend, where its R 2 was 0.97. Based upon results obtained, it can be concluded that the performance of the resulting asphalt can be improved when maleic anhydride was used to treat the added thermoplastics.